EXPLORING THE EFFECTIVENESS OF OFF-THE-JOB TRAINING IN DEVELOPING EDUCATIONAL LEADERSHIP: A SYSTEMATIC LITERATURE REVIEW - Tarso; Nugroho, Adian Purwo; Risnawati Risnawati; Heryuriani , Betty; Siswanto, Deny Hadi (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to explore the role of off-the-job training in enhancing leadership competence in the field of education through a Systematic Literature Review (SLR) approach. The study adopts the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework to screen and analyze literature sourced from three major databases: Web of Science, SCOPUS, and ERIC, with a publication range limited to the years 2015–2025. Out of 439 identified articles, a total of 40 studies were selected based on inclusion criteria, which included document type, thematic focus, and relevance to educational leadership. The data analysis process was conducted using a thematic approach to categorize relevant findings and identify key patterns in the contributions of training. The results indicate that off-the-job training significantly contributes to improving leadership skills by developing educators’ emotional, strategic, and professional competencies. The training is also proven effective in fostering transformational leadership, strengthening teaching practices, and enhancing professional collaboration within educational environments. This study recommends the implementation of continuous and institutionally tailored training programs as a strategic approach to optimize the impact of off-the-job training on the improvement of educational leadership quality in the future